A STYLISTIC ANALYSIS AS VIEWED IN MUKOMA WA NGUGI’S NAIROBI HEAT - Justin, MBULA WA KOLOKOTA (IJRDO- Journal of Educational Research, 2023)
The main objective of this article is to analyze the style used by MukomaWa Ngugi in his novel Nairobi Heat.As matter of fact, it is a detective novel in which the author discusses the themes of transnational violence and crime, betrayal, greed, deception, corruption, and racism. The different aspects listed above, justify the realities that Congolese people live every day. That has constituted a motivation for us to deal with this study.